Resource-saving technologies in the cultivation of walnuts in terms of conomic evaluation methodological approaches - Sadullaevich, Khushmatov Norqul; Boshlarovich, Abror Inobatov (The journal of contemporary issues in business and government, 2021)
This article describes the technological features of walnut cultivation in Uzbekistan, evaluates the possibility of introducing cost-effective agro-technologies in the production process. The authors recommend an evaluation method, emphasizing the need for an economical evaluation of each economical agrotechnology. Resource-saving technologies can be selected in terms of its cost-effectiveness.